Static and fatigue behavior of injection molded short-fiber reinforced PPS composites: Fiber content and high temperature effects. (August 2021) - Solfiti, E.; Solberg, K.; Gagani, A.; Landi, L.; Berto, F.
Highlights: Injection molded specimens directly on dog-bone geometry. Static and fatigue properties both at room temperature and 160 °C. Cyclic parameters for fatigue damage assessment. Abstract: Two different short glass fiber reinforced PPS composites with different fibers content (30% and 40% in weight) were tested upon static and fatigue loading at room temperature. The material with 40% fiber content was also tested at high temperature (160 °C) both in static and fatigue condition. All the specimens were injection molded directly in standardized dog-bone geometry without further cutting or machining. Static tests at three different displacement rates were performed in order to calculate the main static mechanical properties and to observe the strain-rate sensitivity. Fatigue tests for both materials were performed in load control with 0.1 load ratio. The S-N curves are presented in semi-logarithmic coordinates. Some derived cyclic parameters such as the cyclic mean strain and cyclic modulus were calculated to observe the capability to describe the input test variables effect on the damage mechanism. The fracture location distribution along the specimen longitudinal axis were observed and the transverse cross-sections were analyzed by means of optical microscopy in order to correlate the micro-structure and the mechanical properties.